Abraham Lincoln - D'Aulaire, Ingri, 1904-1980.; D'Aulaire, Edgar Parin, 1898-1986. ([San Luis Obispo, CA] : Beautiful Feet Books, 2008)
Text and illustrations present the life of the boy born on the Kentucky frontier who became the sixteenth president of the United States.
Caldecott Medal, 1940.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature